Implementation of Beaver Dichotomy to Differentiate Good and Distressed Firms in Indonesia - Budhidharma, Valentino; Sembel, Roy; Hulu, Edison; Ugut, Gracia S. (Universitas Pelita Harapan, 2023)
The purpose of this study is to determine factors/variables that can differentiate the characteristics of distressed and good firms and propose a new model to explain financial distress in Indonesia. There have been many theories, variables, and estimation methods used by previous studies about early warning signs of financial distress. Determining factors of good and distressed firms uses Beaver's (1968) methodology. The samples used are most sectors in Indonesia’s Stock Exchange from 2005 to 2020, excluding the financial sector. The characteristic results show that good firms have higher NITA, GPTA, CTA, QATA, CATA, WCTA, CCL, RETA, and EBTCL, while distressed firms are better on CFTS, CFTA, CFNW, CFTD, NITS, NINW, NITD, ROE, CLTA, LTLTA, CLLTLTA, QACL, CR, CTS, ITS, CATS, WCTS, NWTS, and TATS.